Legal Accountability of Regional Company Management for Regional Capital Investment in PT. Aman Mandiri - Masrida Masrida; Husen Alting; Suwarti Suwarti (Journal of Social Science, 2023)
This study aims to analyze the effectiveness of regional companies PT. Bahari Aman Mandiri Kota Tidore Islands in the implementation of local government in the era of regional autonomy, and How is legal responsibility for losses incurred by regional companies PT. The research method used in this study is a type of empirical legal research, namely research that looks at the application of laws and regulations in society. The research carried out includes the type of field qualitative research (field research), which is research that emphasizes the completeness of the data collected, namely in the form of primary and skunder data. The results of this study show that the effectiveness of regional companies PT. Bahari Aman Mandiri Tidore Islands City In the implementation of local government in the era of regional autonomy, there are at least two fundamental reasons that are the subject of research that can be the basis that the ineffectiveness of regional companies PT. Bahari Aman Mandiri Kota Tidore Islands in the administration of local government.